KOMPOSISI MEDIA TANAM PADA PEMBIBITAN TANAMAN KARET (Hevea brasiliensis) - Nurlaila; Hendri (JURNAL AGRIMENT, 2019)
The purpose of this reseach was to determine the composition of the right planting media for the growth of rubber plant seeds. This research was conducted for 3 (three) months The State Agricultural Polytechnic at Samarinda. This reseach consists of three levels of media composition treatment namely 75% top soil media and 25% sand (m1), 50% top soil media and 50% sand (m2) and 25% top soil soil media and 75% sand (m3) ). The composition of the planting media of top soil 50% and 50% sand gives better results to the growth of plant height and number of leaves compared to the treatment of the composition of other planting media, namely the composition of the top soil media 75% and 25% sand and the treatment of top soil planting media 25% and 75% sand.